Quality of Warfarin Therapy and Quality of Life are Improved by Self-Management for Two Years - Sølvik, Una Ørvim; Løkkebø, Elisabeth; Kristoffersen, Ann Helen; Brodin, Ellen; Averina, Maria; Sandberg, Sverre (Thrombosis and Haemostasis, 2019)
Background Studies from several countries show that self-management of vitamin K antagonist (e.g., warfarin) therapy reduce the risk of complications compared with conventional management.Objectives The aim of this study was to investigate the quality of warfarin management when patients were transferred from conventional management to self-management in Norway. In addition, quality of life (QoL) before and after 2 years of warfarin self-management was investigated.Materials and Methods The study was longitudinal with a retrospective and prospective design where 126 patients on conventional management of long-term warfarin therapy underwent a 21-week training program of warfarin self-management followed by 2 years of self-management. The outcomes of the study were time in therapeutic range (TTR), the variance of international normalized ratio (INR) values, extreme INR values (INR ≤ 1.5 and ≥ 5), complications, and QoL, comparing the 2-year period of the conventional management with the 2-year period with the self-management.Results The median TTR was higher during self-management compared with conventional management (78.1% vs. 65.9%, respectively, p < 0.001). In addition, self-management resulted in lower INR variance (0.22 vs. 0.33, p < 0.001), reduced percentage of extreme INR values (1.8% vs. 5.3%, p < 0.001), less complications (0% vs. 5.6%), and improved QoL (p < 0.001) compared with conventional management.Conclusion We used five different measures and found improved quality of warfarin self-management 2 years after patients were transferred from the conventional management.
Keywords: international normalized ratio; quality of life; self-management; time in therapeutic range; warfarin